Effects of Computer Learning Program on Preschoolers’ Computer Abilities - Cheah, Eng Khoon (2004)
The objective of this study was to evaluate the effectiveness of an exposure to a computer learning program on preschoolers computing abilities and the factors that affect the acquisition of these skills. Two aspects of computer ability were measured in this study : (i) the ability to name the parts of computer, identify its usage and the function, and (ii) skills in a computer-operating environment. Eighty pre-school students were recruited from a laboratory preschool in Universiti Putra Malaysia (UPM) to participate in this research. Data was collected in three stages: First, the parents of the respondents were required to fill in a questionnaire about their children’s computer knowledge and computer usage at home. Then, all the children were administered a pretest on their computer knowledge and skills in a computer-operating environment at the beginning of the study. Children were stratified by scores after Pretest. High and low scorers were systematically assigned to both experiment and control groups, to ensure that there was no significant difference in the mean scores of both groups at the beginning of the study. The experimental group was given systematic computer lessons for three months, while the control group did not receive any lesson during that time. Third, both groups were post tested on their computer knowledge and skills at the end of the experiment. T-test analysis showed that (1) There is a significant difference in the pre and post test scores of computer ability of subjects in the control group who were not exposed to any computer learning program (t= 5.28, p<0.001); (2) There is a significant difference in the pre and post test scores of computer ability of subjects in the experimental group who were exposed to the computer learning program (t=20.41, p<0.001); Repeated Measures Analyses of Variance showed that (3) Children who were exposed to systematic computer lessons had higher post test scores than children who were not exposed to similar lessons (F1,53 = 103.50, p < 0.001). In order to examine the effectiveness of this program nationwide, further research may focus on comparing the improvement of computer abilities in various kindergartens using the similar teaching method.